超音波診断装置、超音波診断装置の制御方法および超音波診断装置用プロセッサ (2024)
An ultrasound diagnostic apparatus (1, 1A, 1B) comprising: a B-mode processing (6) unit that generates a B-mode image in which at least a blood vessel is imaged on the basis of a reception signal obtained by transmitting and receiving ultrasonic waves to and from a subject;a display device (9) that displays the B-mode image; a vascular wall detection unit (10) that detects a vascular wall by analyzing the B-mode image; a gate setting unit (11) that sets a Doppler gate in the blood vessel on the B-mode image; a Doppler processing unit (7) that acquires Doppler data in the Doppler gate; a blood flow velocity calculation unit (13) that calculates a blood flow velocity on the basis of the Doppler data; and a blood flow rate measurement unit (12) that measures a blood flow rate on the basis of the vascular wall detected by the vascular wall detection unit (10) and the blood flow velocity calculated by the blood flow velocity calculation unit (13), wherein the blood flow rate is automatically measured on the basis of a fixed start trigger, a fact that the blood vessel imaged in the B-mode image generated by the B-mode processing unit (6) is changed from a short-axis image to a long-axis image is used as the start trigger.